2016
DOI: 10.1063/1.4949507
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of limited-diffractive and limited-dispersive X-waves generated by finite radial waveguides

Abstract: In this work, we analyze the spatial and temporal features of electromagnetic X-waves propagating in free space and generated by planar radiating apertures. The performance of ideal X-waves is discussed and compared to practical cases where the important effects related to the finiteness of the radiating aperture and the wavenumber dispersion are taken into account. In particular, a practical device consisting of a radial waveguide loaded with radiating slots aligned along a spiral path is considered for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 42 publications
4
52
0
Order By: Relevance
“…Note that similar results have been obtained for zeroth-order X-waves in Ref. 25. As a consequence, the nondiffractive range also represents the distance for which the OAM is effectively carried by the pulse.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Note that similar results have been obtained for zeroth-order X-waves in Ref. 25. As a consequence, the nondiffractive range also represents the distance for which the OAM is effectively carried by the pulse.…”
supporting
confidence: 83%
“…Such a standing-wave distribution is inherently narrow-band 10 , whilst the generation of efficiently confined localized pulses requires wideband capabilities, as discussed in detail in Ref. 25. However, it has recently been demonstrated 27 that an inward traveling-wave aperture distribution can generate a Bessel beam in a biconical region close to the axis of symmetry of the aperture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…therein). Just very recently, theoretical and numerical results have been reported in [7][8][9], whereas experimental results just appeared in [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, it has been shown that leaky waves (LWs) can profitably be used for generating Bessel beams with considerably narrower spot-sizes in both microwave [12,13] and millimeter-wave ranges [1]. However, both these leaky-wave antennas (LWAs) exhibit a narrow operating fractional bandwidth, and thus they are not suitable for the generation of polychromatic nondiffracting waves, such as XWs [7]. This narrow-band feature is due to the resonant character of the radiation mechanism, which is typically based on the superposition of an outward and an inward cylindrical wave [14].…”
Section: Introductionmentioning
confidence: 99%